A randomised controlled trial of twelve months protein supplementation on muscle mass and strength in elderly women - Meng, Xingqiong (Rosie) (Curtin University, 2010)
Background. Aging is associated with progressive loss of muscle (sarcopenia), which can lead to reduced muscle strength and an increased risk of falls. Sarcopenia exists in otherwise healthy elderly people and its aetiology is not fully understood. Many epidemiological studies have shown that high protein intake is associated with preserving muscle mass and strength in the elderly. To date there have been few randomized trials of sufficient duration and power to examine the effects of dietary protein supplement on muscle mass and strength in the elderly. The objective of this study was to examine the effectiveness of whey protein supplementation on preventing sarcopenia in elderly women.Methods. A population based, one-year randomized, double blind and placebo controlled trial of protein supplementation was conducted on 219 community-dwelling ambulant women aged 70 to 80 years. Participants in the protein supplement group (n=109) consumed a drink daily which contained 30 g of protein. The control group (n=110) consumed a drink with the same energy (kilojoules) but only contained 2 g of protein. Assessments were taken at baseline and one year. Body composition was assessed by anthropometry and whole body dual-energy x-ray absorptiometry. Peripheral quantitative computer tomography was used to assess calf muscle crosssectional area. Hand grip, ankle dorsiflexion, knee and hip strengths were assessed using an isokinetic dynamometer. Mobility was assessed by the ‘Timed Up and Go’ test. Standing balance was assessed by the Romberg test. Dietary intake was assessed by a 3-day weighed food record. Compliance with the dietary intervention was assessed by 24-hour urinary nitrogen and by counting the returned empty supplement containers. Serum insulin-like growth factor one (IGF-1) was also measured.Results. One-hundred and ninety-five participants aged 74±3 years completed the one year trial. There were no significant differences in baseline characteristics between the protein supplemented group (n=100) and control group (n=95). Compared to their baseline values, both groups significantly increased whole body lean mass (protein group: +1.6%, p<0.05; control group: +2.3%, p<0.05), appendicular lean mass (protein group: +1.3%, p<0.05; control group: +1.8%, p<0.05), body weight (protein group: +0.8%, p<0.05; control group: +1.5%, p<0.05) and knee strength (protein group: +31%, p< 0.05; control group: +36%, p<0.05) after one year. The total fat mass increased from baseline only in the control group (protein group: +0.7%, p=0.19; control group: +1.5%, p<0.05). There were however no significant differences between the two drink groups in any of the above mentioned parameters. Over one year serum IGF-1 increased significantly in the protein group but decreased in the control group (protein group: +7.6%, p = 0.006; control group: -1.0%, p = 0.005), and the changes were significantly different between two drink groups (p = 0.006). The protein supplement also showed a protective effect on preserving balance function at one year. The prevalence of ‘poor standing balance’ and ‘fall rates’ were significantly increased in the control group at one year.Conclusion. Muscle mass and strength increased equally in both drink groups. Although fat mass only increased in the control group at one year there was no statistically significant difference in the changes in fat mass between the two groups due to the wide variance in response. Protein supplementation resulted in an increased serum IGF-1 level at one year compared with the control group. These data are consistent with the concept that in this age group increased energy intake regardless of the macronutrient composition of the supplements improves muscle mass and function. It is possible that achieving this through increased protein rather than carbohydrate may prevent the increase in fat mass noted with the carbohydrate supplement for the control drink perhaps by an effect of the protein to increase serum IGF-1. The metabolic significance of this remains to be explored.